2018
DOI: 10.1515/revneuro-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Acute anxiety disorder, major depressive disorder, bipolar disorder and schizophrenia are related to different patterns of nigrostriatal and mesolimbic dopamine dysfunction

Abstract: Dopamine (DA) receptor and transporter dysfunctions play a major role in the pathophysiology of neuropsychiatric diseases including anxiety disorder (AD), major depressive disorder (MDD), bipolar disorder (BD) in the manic (BDman) or depressive (BDdep) state and schizophrenia (SZ). We performed a PUBMED search, which provided a total of 239 in vivo imaging studies with either positron emission tomography (PET) or single-proton emission computed tomography (SPECT). In these studies, DA transporter binding, D1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 232 publications
0
19
0
Order By: Relevance
“…Apart from dopaminergic dysfunction, which can manifest with different patterns in the nigrostriatal and mesolimbocortical pathways in BD (33) and PD, the two disorders might potentially share the involvement of additional pathophysiological processes. Impairment in the serotoninergic and glutamatergic circuitries has been classically described in BD disorder (34) and is involved in certain motor and non-motor symptoms of PD such as tremor (35) and mood dysfunction (36).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from dopaminergic dysfunction, which can manifest with different patterns in the nigrostriatal and mesolimbocortical pathways in BD (33) and PD, the two disorders might potentially share the involvement of additional pathophysiological processes. Impairment in the serotoninergic and glutamatergic circuitries has been classically described in BD disorder (34) and is involved in certain motor and non-motor symptoms of PD such as tremor (35) and mood dysfunction (36).…”
Section: Discussionmentioning
confidence: 99%
“…According to the monoamine hypothesis, monoamine neurotransmitters, including serotonin (5-HT), dopamine (DA), and norepinephrine (NE), have always been the key aspects in mood disorders. Although previous genetic, biological and pharmacological studies confirmed the important role of 5-HT in MDD (7,9), accumulating evidence suggested the contribution of dysregulated DA and NE transmission on both MDD and BD (10)(11)(12). DA and NE play an important role not only in cognitive function, but also in emotion regulation (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of a striatal hyperdopaminergy is reinforced by data that show that antipsychotics all exhibit the property to block DAergic D2 receptors to some degree (Kaar et al, 2020). As regards striatal hyperdopaminergic activity, meta-analyses of brain imaging studies suggest an increase in DA release in either both the dorsal and ventral parts of the striatum (Nikolaus et al, 2019) or only in the dorsal striatum (mainly in the associative striatum)(McCutcheon et al, 2018). However, subdivisions of the ventral striatum and differential changes in these sub-territories have never be reported in such meta-analyses, whereas preclinical studies support the view that the shell subdivision of the nucleus accumbens (Nacc), part of the ventral striatum, is the shared anatomical target for all antipsychotics (typical and atypical antipsychotics), with the dorsolateral striatum being the preferential target for typical antipsychotics (Deutch et al, 1992, Merchant and Dorsa, 1993, Mo et al, 2005; Jennings et al, 2006; Natesan et al, 2006; Collins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%